2009
DOI: 10.1359/jbmr.080912
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in Sex Hormone Genes Influences Heel Ultrasound Parameters in Middle-Aged and Elderly Men: Results From the European Male Aging Study (EMAS)

Abstract: Genes involved in sex hormone pathways are candidates for influencing bone strength. Polymorphisms in these genes were tested for association with heel quantitative ultrasound (QUS) parameters in middle-aged and elderly European men. Men 40-79 yr of age were recruited from population registers in eight European centers for the European Male Aging Study (EMAS). Polymorphisms were genotyped in AR, ESR1, ESR2, CYP19A1, CYP17A1, SHBG, SRD5A2, LHB, and LHCGR. QUS parameters broadband ultrasound attenuation (BUA) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 54 publications
1
15
0
2
Order By: Relevance
“…Only minor effects of this polymorphism on circulating T and E 2 levels are apparent, reaching statistical significance with large sample sizes. We have reported previously from the EMAS cohort associations of the AR exon 1 CAG repeat polymorphism with endocrine and metabolic parameters (23), and of AR exon 1 CAG repeat and other polymorphisms with heel ultrasound parameters (8). Other genes with polymorphisms associated with androgen and/or estrogen levels in men include SHBG (28), CYP17 (29), CYP19A1 (30), 17␤HSD5 (31), and uridine diphosphate glucuronyltransferase 2B7 (UGT2B7) (32), but many potentially important polymorphic influences have apparently not yet been identified.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Only minor effects of this polymorphism on circulating T and E 2 levels are apparent, reaching statistical significance with large sample sizes. We have reported previously from the EMAS cohort associations of the AR exon 1 CAG repeat polymorphism with endocrine and metabolic parameters (23), and of AR exon 1 CAG repeat and other polymorphisms with heel ultrasound parameters (8). Other genes with polymorphisms associated with androgen and/or estrogen levels in men include SHBG (28), CYP17 (29), CYP19A1 (30), 17␤HSD5 (31), and uridine diphosphate glucuronyltransferase 2B7 (UGT2B7) (32), but many potentially important polymorphic influences have apparently not yet been identified.…”
Section: Discussionmentioning
confidence: 90%
“…Genotyping of the SHBG repeat, SRD5A2 repeat, and the CYP19A1 indel was described previously (8). Genotyping of V-LHB was based on differential immunoreactivity of wild-type (WT) and V forms of LH in serum samples, as described before (9).…”
Section: Genetic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro functional analyses suggested that rs1062033, which is located »12 kb upstream of the translation initiation site, represents a true regulatory polymorphism (Riancho et al 2009). Finally, signiWcant associations were observed between multiple SNPs in a LD block within CYP19A1 with reduced ultrasound BMD and bone strength in middleaged and elderly men (Limer et al 2009). …”
Section: Cyp19a1mentioning
confidence: 99%
“…The hypothesis that this SNP may aVect gene expression by creating a Sp1 binding site (Carey et al 1994) was not supported by in vitro studies (Nedelcheva Kristensen et al 1999). Several studies have analyzed whether this SNP is associated with osteoporosis, but they have yielded inconsistent results Limer et al 2009;Somner et al 2004;Tofteng et al 2004a;Valero et al 2005;Yamada et al 2005b;Zarrabeitia et al 2007;Zmuda et al 2001). Here, we focus on the three studies that analyzed >1,000 subjects.…”
Section: Cyp17a1mentioning
confidence: 99%